The Network Constellation of Personality and Substance Use: Evolution from Early to Late Adolescence. Issue 6 (20th March 2020) - Afzali, Mohammad H.; Stewart, Sherry Heather; Séguin, Jean R.; Conrod, Patricia
Abstract: There is a well‐established link between substance use and four personality traits of anxiety–sensitivity, hopelessness, impulsivity, and sensation‐seeking. However, construct‐level models of personality may conceal indicator‐level personality–outcome associations. The current study aims to investigate evolution of the network constellation of personality and cannabis/alcohol use from early to late adolescence. Data comes from the longitudinal Co‐Venture cohort (N = 3800). Personality indicators, measured by Substance Use Risk Profile Scale (SURPS) items, and the frequency of cannabis/alcohol use were assessed at four consecutive years (13–17 years old). Network constellations of the SURPS items and cannabis/alcohol use were estimated using Bayesian Gaussian graphical models at four time points. Results highlighted the age‐specific associations between personality indicators and substance use. The positive role of the sensation‐seeking trait (e.g. attitude towards transgression) was constant, whereas the positive role of hopelessness indicators (e.g. not being enthusiastic about future) and the negative role of anxiety–sensitivity indicators (e.g. fear of having unusual body sensations) were more prominent at early adolescence. The current study provides a novel perspective on the network structure of personality and substance use in adolescence and suggests substance‐specific and age‐adjusted targets in intervention efforts . © 2020 European Association of Personality Psychology